Green thoughts, green shades : essays by contemporary poets on the early modern lyric - Post, Jonathan F. S., 1947- (University of California Press, 2002)
Green Thoughts, Green Shades is a strikingly original book, the first and only of its kind. Edited and introduced by noted seventeenth-century scholar Jonathan Post, it enlists the analytic and verbal power of some of today's most celebrated poets to illuminate from the inside out a number of the greatest lyric poets writing in English during the sixteenth and seventeenth century.